HUBUNGAN KEBUGARAN JASMANI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMP NEGERI 3 UNGARAN - Reza, Deswitama Fahri; Pujianto, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to ascertain how students' academic performance as shown by their report card scores and their degree of physical fitness as assessed by the Indonesian Physical Freshness Test (TKJI) are related. 164 participants from five distinct junior high school classes participated in this study, which employed quantitative correlation as its methodology. The TKJI test, which gauges physical health, and semester report card scores, which show intellectual success, are among the tools utilized. The Pearson correlation test and the t-test were used to continue the investigation after the results of the normality and homogeneity test indicated that the data were distributed normally and uniformly. With a correlation coefficient of r = 1.00 and a significance value of p = 0.000, the correlation test findings demonstrated a very strong and significant association between the TKJI score and report card score. The TKJI scores of the various student groups differed significantly, according to the t-test, however the report card scores did not differ significantly. We can conclude that students' learning achievement is influenced by their level of physical fitness. Therefore, in order to assist the overall improvement of student learning outcomes, physical coaching through sports activities in schools needs to be maximized.